Plant Growth Regulators (PGRs) Study for Root and Bud Induction on Stem Cuttings of Stevia rebaudiana - Apriani, Ike; Sonia Adiba; Dawani; Nurseha, Tito; Fatiqin, Awalul; Yessy Velina (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2024)
The Stevia plant is used as a low calorie natural sweetener known as